Cultural Representations of Climate: The 1998 Montreal Ice Storm. (January 2016) - Kannenberg, Christina
Abstract : Despite much excellent work on representations of the North and nordicity in Québécois literature, scholars have not yet explored the relationship between the ice storm of 1998 and cultural representations. This article analyzes public spaces, communal activities, and narration in two fictional ice storm narratives: the short story "Banana Chaudfroid" by Monique Proulx (1999) and Pierre Szalowski's 2007 novel Le froid modifie la trajectoire des poissons. The ice storm changes the social practices of city dwellers in both texts, forcing them to participate in communal activities with people whom they have never met, usually their own neighbors. Narrative, both the television news narratives represented within the texts as well as the novel and short story themselves, participate in the healing process by shaping the collective memory of the ice storm. The role of public spaces is crucial in both Proulx and Szalowski's texts as emergency shelters and even private homes become semi-public spaces when they are shared by strangers. The texts use Foucault's notion of heterotopia to explore the spatiality of the ice storm that grips their city, and the appropriation of space by the characters to claim their own place in Montreal.